2018
DOI: 10.1017/s0022149x18000615
|View full text |Cite
|
Sign up to set email alerts
|

Antifilarial activity of azadirachtin fuelled through reactive oxygen species induced apoptosis: a thorough molecular study on Setaria cervi

Abstract: Efficacious therapeutic strategies against lymphatic filariasis are always sought after. However, natural products are a promising resource for developing effective antifilarial agents. Azadirachtin, a significant tetranortriterpenoid phytocompound found in Azadirachta indica, was evaluated in vitro for antifilarial potential against the filarial parasite Setaria cervi. Dye exclusion and MTT assay confirmed the antifilarial potential of azadirachtin against S. cervi with a median lethal dose (LC50) of 6.28 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…After complete fixation, dehydration in graded alcohol was done and finally embedded in molten paraffin. 5μm of adult parasite tissue sections were prepared for hematoxylin-eosin staining [18, 22].…”
Section: Methodsmentioning
confidence: 99%
“…After complete fixation, dehydration in graded alcohol was done and finally embedded in molten paraffin. 5μm of adult parasite tissue sections were prepared for hematoxylin-eosin staining [18, 22].…”
Section: Methodsmentioning
confidence: 99%
“…This inspired a study reporting on the efficacious therapeutic activity of Azadirachtin against LF. It further indicated that a significant tetranortriterpenoid phytocompound found in Azadirachta indica , showed efficacies against the filarial parasite Setaria cervi in vitro 34 . Thus, remedies for LF pathology should be directed towards interventions that are known to invoke less or moderate inflammation.…”
Section: Constituents Of Natural Plant Products Against Lfmentioning
confidence: 99%
“…Azadirachtin effectively inhibits the development of S. frugiperda by inducing apoptosis. 429,430 By inhibiting larval feeding, and reducing the digestion and absorption of nutrients in the midgut, azadirachtin inhibits the larval growth and development of Spodoptera litura and Bactrocera dorsalis. 431,432 By exerting immunosuppressive effects, azadirachtin inhibits the growth of Sarcophaga (Liopygia) argyrostoma and esh ies.…”
Section: †)mentioning
confidence: 99%